The Role of Knowledge Management and Dynamic Capabilities on Sustainable Competitive Advantage in Indonesian Private Higher Education - Elistia Elistia; Dedi Purwana; Karuniana Dianta Sebayang; Mohammad Sofwan Effendi; Corry Yohana (Qubahan Academic Journal)
This study investigates the impact of knowledge management on dynamic capabilities and sustainable competitive advantage in Private Higher Education Institutions (PHEIs) in Indonesia. Drawing on the knowledge-based view and dynamic capabilities framework, the study employs a structural equation modeling approach to analyze data collected from 92 leaders of 10 PHEIs in Jakarta, Indonesia. The findings reveal that knowledge management has a significant positive effect on both dynamic capabilities and sustainable competitive advantage, with dynamic capabilities partially mediating the relationship between knowledge management and sustainable competitive advantage. The study contributes to the literature by providing empirical evidence on the interplay between knowledge management, dynamic capabilities, and sustainable competitive advantage in the context of PHEIs in Indonesia. The findings of this research suggest that the establishment of a framework and the facilitation of knowledge integration among learning, research, and community service are crucial for effective knowledge management governance among students, universities, and society. The study also highlights the need for future research to validate the findings in different contexts and explore the boundary conditions of the relationships examined.